Analisis sikap petani terhadap pelaksanaan sekolah lapang pengelolaan tanaman terpadu (SL-PTT) dan peningkatan produksi padi - Prihono Prihono; Murdani Murdani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
This study aims to determine how farmers' attitudes towards the implementation of integrated crop management (SLPTT) field schools towards increasing paddy rice production and its relationship with farmer rice productivity. The research method uses a descriptive quantitative approach, the method of data analysis uses variance analysis and to distinguish differences between groups using the Tukey test because the number of variables is more than two. The results of the processing and analysis of research data show that the average farmer has a positive attitude or response to the implementation of the SLPTT (average attitude score of 76.47%) and an increase in farmer's rice production by 16.39% (up 0.73 tons/ha of dry unhusked rice), from 4.48 tons/ha milled dry grain to 5.2 tons/ha milled dry rice). The results of statistical tests show that there is a positive correlation/relationship between all indicators of farmer's attitude and the productivity produced. The highest correlation is obtained from the indicator 'training method' with the correlation criteria 'close to perfect', the correlation coefficient value is 0.900. Overall attitudes of farmers towards implementing SLPTT have a weak positive correlation (correlation coefficient value 0.145) with lowland rice productivity. Farmer rice productivity increased but the production achieved was still below the NTB province's target of 5.42 tons/ha of dry milled rice with an increase in production of 0.5-1.0 tons/ha dry milled rice or 4.77%.